Relevance of Moral Education - Aramavičiūtė, Vanda (Acta Paedagogica Vilnensia, 1991)
According to the Lithuanian conception of the general secondary education (1989), the article points out that moral education should become the core of all education, whose main objective is the education of an active moral position. At the same time it is noted that the moral position is a complex phenomenon involving the spheres of moral consciousness and moral behavior. The theoretical part of the article briefly discusses the content of moral position, defines the criteria for describing the level of moral position. Empirical survey of the senior pupils’ moral position are based on these criteria. The survey aimed to: 1) determine what moral values and to what level pupils have permeated; 2) distinguish between the general and specific features of the moral position specific to students of different types of schools; 3) distinguish the social and pedagogical factors influencing the internalization of moral values; 4) describe the essential conditions determining for moral character of the above factors; 5) identify the key position of moral education in the direction of the various types of schools.
Keywords: moral education; moral position; moral values; internalization of values